China's Market Distortions and the Impact of the Covid-19 Crisis - Jürgen Matthes (CESifo Forum, 2020)
Subsidization in China is pervasive at numerous levels of government and appears to be an inherent element of Chinese state capitalism. Despite a severe lack of transparency, the available information seems to suggest that the extent of Chinese subsidies is extraordinarily large. Moreover, the resulting overcapacities could lead to considerable and increasing distortions on the world market in certain sectors. An initial assessment of the potential effects of the Covid-19 crisis on China's industrial policy model does not suggest a major change in subsidization policy. This constellation bodes ill for the future of the multilateral trading system.
Keywords: 330